IMMEDIATE RESULTS OF COMPLEX TREATMENT OF CHILDREN WITH CHRONIC TONSILLITIS AND CHRONIC ADENOIDITIS ASSOCIATED WITH CMV AND EBV - Mukhamadieva L.A; Rustamova G.R; Kudratova Z.E. (Western European Studies, 2024)
Most researchers have concluded that cytomegalovirus infection may contribute to the exacerbation of many chronic and recurrent diseases. In addition, they can cause direct, autoimmune reactions in the body [2,4,5]. GossmanW. G et al [2018] defined several forms of cytomegalovirus infection in the organism depending on the course of the infection: primary infection if no cytomegalovirus has been previously identified in a person, re-infection or reactivation if CMVI has been previously identified in the organism; the course can be acute, latent or chronic in congenital or acquired CMVI [6,7,8,9]. In acute CMV infection, all tissues are affected. NigroG. et al [2015] found that cytomegalovirus infection, if T-cell immunity is reduced in the organism, can invade the body for a long time and then the infection can manifest itself as a subacute course [10,11]. Jones R. P. et al [2014] and Kallemeijn1 M. J.[2017]. et al in their studies found that children with congenital cytomegalovirus infection have a very high incidence of death, neurological impairment and in addition HIV infection progresses faster in them
Keywords: researchers; HIV infection; cytomegalovirus; infection